Circulation of Brucellaceae, Anaplasma and Ehrlichia spp. in borderline of Iran, Azerbaijan, and Armenia - Rahimeh Abdoli; Hasan Bakhshi; Sedigheh Kheirandish; Faezeh Faghihi; Asadollah Hosseini-Chegeni; Mohammad Ali Oshaghi; Zakkyeh Telmadarraiy; Mohammad Mehdi Sedaghat (Asian Pacific Journal of Tropical Medicine, 2021)
Objective: To estimate the infection of ticks to Anaplasma, Ehrlichia, Babesia, Theileria, and Brucellaceae using molecular methods in borderline of Iran, Azerbaijan, and Armenia. Methods: Totally, 2 022 ticks were collected from different livestock. Then, species were diagnosed under stereomicroscope according to valid morphological keys. Tick DNA was extracted followed by PCR to detect Anaplasma, Ehrlichia, Theileria, Babesia and Brucellaceae infection in ticks. Results: A total of 498 males [24.62% (95% CI 22.76%-26.57%)], 741 females [36.64% (95% CI 34.54%-38.79%)], 782 nymphs [38.67% (95% CI 36.55%-40.84%)] and 1 larva [0.04% (95% CI 0.00%-0.28%)] were identified. Among identified samples, we found four genera including Hyalomma, Rhipicephalus, Haemaphysalis, and Dermacentor. Molecular assay revealed that the prevalence of ticks to Anaplasma or Ehrlichia, and Brucellaceae was 22.02% (95% CI 16.01%-29.06%) and 15.03% (95% CI 9.43%-22.26%), respectively. Phylogenetic analysis showed that the identified Anaplasma sp. had the most similarity with Anaplasma centrale, Anaplasma platys, Anaplasma camelii, and Anaplasma phagocytophilum, submitted in GenBank. Furthermore, the detected Ehrlichia sp. and Brucellaceae bacterium had the most similarity with Ehrlichia ruminantium and Mycoplana peli, respectively. However, no sign of the presence of Theileria and Babesia spp. was seen in the studied samples. Conclusions: Anaplasmosis, ehrlichiosis and brucellosis should be considered as important health threats in northwestern Iran and consistent monitoring on infection of ticks and livestock should be performed regularly.